Surface functionalization of the AA2017 aluminum alloy powder for use in additive manufacturing - Batistão, Bruna Fernanda (Universidade Federal de São Carlos, 2026)
Additive manufacturing (AM) of high-strength aluminum alloys faces challenges due to their high reflectivity, high thermal conductivity, poor powder flowability, and susceptibility to solidification cracking during laser powder bed fusion (L-PBF). These issues hinder stable powder spreading, full densification, and microstructural control, thus limiting their industrial applicability. In this context, the objective of this work was to investigate the surface functionalization of gas-atomized AA2017 powder – an aircraft Al-Cu-Mg alloy from the 2xxx series (EN AW-2017, AlCu4MgSi) – as a viable strategy to improve flowability, laser absorption, and solidification behavior during L-PBF processing. Two approaches were explored: chemical etching using acidic (HNO3) and basic (NaOH) solutions, and the addition of TiC particles with different sizes and concentrations. Chemical etching treatments improved powder flowability and laser energy absorption but promoted the formation of oxide layers on powder surface, which increased oxidation-related porosity in the as-built samples. Conversely, the addition of TiC effectively modified the alloy solidification, promoting strong microstructural refinement and a columnar-to-equiaxed transition, along with the formation of coherent Al3Ti particles, resulting in dense and crack-free samples. A key and novel outcome of this work is that fine micrometer-sized TiC particles (<4 μm) outperformed nanoparticles in enhancing the microstructure and mechanical properties of the AA2017 alloy. Although nanoparticles can theoretically provide greater grain refinement and strengthening, their strong tendency to agglomerate limited their efficiency. Therefore, the addition of fine micrometer-sized TiC particles proved to be a practical and efficient route to improve the processability of high-strength aluminum alloys by L-PBF, while also being safer to handle than nanoparticles. Additionally, to the best of the author's knowledge, this work provides important and new insights into the mechanisms governing grain refinement, strengthening, and discontinuous yielding behavior in TiC-modified 2xxx series aluminum alloys in L-PBF for the first time in the literature.
Funcionalização da superfície do pó da liga de alumínio AA2017 para uso em manufatura aditiva
Keywords: Fusão seletiva a laser em leito de pó; Liga de alumínio AA2017; Funcionalização da superfície do pó; Ataque químico; Adição de partículas; Laser powder bed fusion; AA2017 aluminum alloy; Surface functionalization of the powder; Chemical etching; Particle addition; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA; 9. Indústria, Inovação e Infraestrutura